Enhancing Teachers’ Competence in Developing Deep Learning BasedLesson Plans Using Flipbook Media Through Training at SD NegeriInpres Sereh - Tipuk Widiastuti; Yari Dwikurnaningsi; Herry Sanoto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study examines the effectiveness of a flipbook-assisted training model in enhancing teachers’ competence in designing deep learning–based lesson plans within the context of elementary education. The research is grounded in the growing demand for integrating pedagogical and digital competencies to support meaningful learning aligned with contemporary curriculum reforms. A quantitative approach with a quasi-experimental design was employed, involving 18 elementary school teachers participating in a structured training program. Data were collected through pre-test and post-test assessments, observations, questionnaires, interviews, and document analysis of lesson plans. The findings reveal a significant improvement in teachers’ competence, as indicated by increased post-test scores and the enhanced quality of lesson plans. Teachers demonstrated a shift from procedural and teacher-centered approaches toward more student-centered, structured, and reflective instructional designs. The use of flipbook media played a crucial role as a cognitive scaffold, enabling teachers to organize learning components more coherently and effectively. Furthermore, iterative training cycles supported sustained improvement through continuous reflection and refinement. These results suggest that integrating digital scaffolding with deep learning pedagogy provides a robust and practical model for teacher professional development. The study contributes theoretically by offering an integrated framework that bridges pedagogy and technology, and practically by presenting a replicable training model that can support sustainable instructional improvement in diverse educational contexts.